Vibration analysis and topology optimization of the header of full-feeding rice combine harvester - Tang, Han; Xu, Changsu; Zhu, Jianhua; Guan, Rui; Wang, Jinwu (International Journal of Agricultural and Biological Engineering, 2023)
The header frame of full-feeding rice combine harvester was characterized by severe vibration due to the excitation force generated by the movement of each working part. In order to solve the problem, the parametric model of header frame was established, and the accuracy of the finite element model was verified by comparison the results of the free modal analysis and free vibration modal test based on Eigensystem Realization Algorithm (ERA). Then the constrained modal frequencies were calculated and compared with the external excitation source frequencies, the results showed that the first and eighth order modal natural frequencies were coupled with the excitation frequencies of the threshing cylinder and the engine respectively, which was apt to resonate. To avoid resonance and achieve lightweight design, topology optimization and the finite element analysis was carried out. The optimization results showed that the strength and rigidity meet the requirements and the weight was 14.17% lower than before. The first and eighth order modal natural frequencies were far away from the excitation frequencies range of threshing cylinder and engine, and the frequencies were far away from the range of each excitation frequency, which effectively avoided the occurrence of resonance. Field experiments showed that the peak value of the vibration acceleration in the three directions of the 8 measuring points of the optimized header frame was significantly reduced, which effectively reduced the vibration of the header frame during harvest. This study provides a method for obtaining the vibration characteristics of key components of agricultural machinery, and provides a reference for the weight and vibration reduction of header frame of rice, wheat, rape and other crop combine harvesters.Keywords: eigensystem realization algorithm, modal analysis, free modal test, topology optimization, lightweight, field experimentDOI: 10.25165/j.ijabe.20231604.7096Citation: Tang H, Xu C S, Zhu J H, Guan R, Wang J W. Vibration analysis and topology optimization of the header of full-feeding rice combine harvester. Int J Agric & Biol Eng, 2023; 16(4): 96-108.